The Sensus Literalis and the Trinity in the English Enlightenment - Ney, David (Pro ecclesia, 2020)
The doctrine of the Trinity was fiercely contested in the English Enlightenment. This debate is of interest not simply because of the doctrinal articulations of the belligerents or their various approaches to the Scriptural text, but because it led to the consolidation of a precise understanding of the relationship between the sensus literalis and doctrine for Trinitarians and Antitrinitarians both. Antitrinitarians of the English Enlightenment came to agree that the sensus literalis could be isolated by identifying the singular referent of each Scriptural word, but Trinitarians came to insist, to the contrary, that Scriptural words always refer within a larger canonical framework.